UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MODEL PEMBELAJARAN RADEC PADA MATERI ENERGI DAN PERUBAHANNYA DI KELAS III SDN 2 TAMBAKSOGRA - Lutpi Yandi Heryana; Badarudin (STKIP Subang, 2024)
Changes. The research occurred in two cycles, each cycle consisting of two meetings through the stages of planning, implementation, observation, and reflection. Students of SDN 2 Tambaksogra, Banyumas there are 11 girls and 5 boys in class III who are the focus of this research. The research instruments used are observation sheets, learning outcomes tests. The results showed that the RADEC Learning Model could improve students' cognitive, affective, psychomotor learning outcomes which were marked by an increase in each cycle. cognitive learning outcomes increased from 65.63% to 87.50%. Then affective learning outcomes increased from 67.44% to 85.12% and psychomotor learning outcomes also increased from 68.75 to 85.41%, the success indicator of learning outcomes in cycle II through the application of the RADEC Learning Model (Read, Answer, Discuss, Explain, Create) has been met. From the above research in applying the RADEC Learning Model on energy material and its changes can improve student learning outcomes.